MAPPING FAMILY READINESS ON ELEMENTARY SCHOOL STUDENTS’ ONLINE LEARNING CONTINUITY DURING COVID-19 PANDEMIC - Nunu Mahmud Firdaus (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
The purpose of writing this article is to understand the important role of adult education during COVID-19 pandemic which occurred starting in March 2020 so that the government instructs schools to carry out teaching online (online) as an effort to prevent transmission of the disease. The author observes that during online learning students and teachers develop their knowledge of the network system without getting much training which tends to rely on self-learning, for students, especially the success of online learning is very much influenced by family education where interaction is more dominant with family at home, the authors assume informal education affects student success in learning , the writing of this research is intended so that readers and public can know that mapping informal education is an important part of the success of school students in implementing online learning. In the results of interviews with the authors' parents, the writer got the information that family readiness in guiding children to study at home is an urgency that must be implemented.